Pathways to gender equality: A configurational analysis of childcare instruments and outcomes in 21 European countries. (24th January 2020) - Lauri, Triin; Põder, Kaire; Ciccia, Rossella
Abstract: The ability to produce desired outcomes represents an important basis of the legitimacy of social policies. Nonetheless, policy outcomes have not systematically figured in the analysis of childcare regimes despite growing political interest in issues such as female employment, gender wage gap, and men's involvement in childcare. In this article, we use fuzzy set qualitative comparative analysis to investigate the relationship between the configuration of policy instruments, attitudes toward childcare and outcomes in 21 European countries. Our results show that there is only one mix of policy instruments consistently linked with positive gender equality outcomes and this route has the quality of the universal caregiver model. It also demonstrates that both a combination of policy instruments and favorable attitudinal factors are necessary to produce desirable outcomes in the gender division of paid work and unpaid childcare.